Propagation and early establishment of red butterfly plant (Cristia vespertilionis) as affected by cutting position, rooting media and shade level - Amjad Farhan bin Ashraf Farhan
An enthralling plant species acknowledged as Christia vespertilionis had been associated with its remarkable capabilities to cure vast range of illnesses, which had prearranged it to amass prodigious attention from the public nationwide. The overtures of using Christia vespertilionis as medicinal plants may ascertain to be quite auspicious, despite the lack of availability for both supply and appropriate technique for commercialization. The absence of agronomic studies for this plant had prominently paved to a scarcity in sustainable supply and productivity. Hence, the objectives of this study were to highlight the plants from its agronomical standpoints in which to assess the preeminent cutting strata and its propagation media, the aftermath of the finest growing media as well as to evaluate the superlative shade requirement for the plant. In the first study, the stock plants were allocated into four treatments of cutting strata: PI, P2, P3 and P4 whereby PI was the bottommost plant part while P4 being the uppermost. As for the study of propagation media, plant cuttings were disseminated amongst cocopeat (CP), burnt rice husk (BRH) and Holland peat (HP) which comprised of 6 treatments: CP, 3 CP: I BRH, 1 CP: 1 BRH, 1 CP: 3 BRH, BRH and HP. On the other hand, both soil based and soilless media studies were incorporated as growing media with each consisted of six treatments. The soil based media had integrated topsoil (TP), sand (SD) and Holland peat (HP): TP, 7 TP: 2 SD, 7 TP: 4 SD, 7 TP: 6 SD, 7 TP: 8 SD and HP whereby the soilless media had embodied cocopeat (CP), burnt rice husk (BRH) and Holland peat (HP): CP, 3 CP: I BRH, 1 CP: 1 BRH, 1 CP: 3 BRH, BRH and HP. In terms of shade intensity study, four treatments were employed: Ll (0%), L2 (50%), L3 (70%) and L4 (90%). In addition to that, the parameters recorded in this study had comprised of morphological, physiological and physicochemical data. Throughout the study, it was highlighted that the preeminent cutting strata and propagation media were the treatment P3 (third cutting strata) and treatment C4 (1 CP: 3 BRH). Additionally, the most apposite growing media was soil based media which was treatment T2 (7 TP: 2 SD), whereas the most pertinent shade intensity was established with treatment L4 which had incorporated 90% shade for the plant to proliferate. Last, but not least, the findings had pointed out that the optimization of abiotic factors such as plant cuttings, plant media and shade intensity can be translated into better quality and productivity of C. vespertilionis plants.